1997
DOI: 10.1093/bja/79.1.128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine and pentobarbitone on acetylcholine release from the rat frontal cortex in vivo

Abstract: We have studied the effects of ketamine and pentobarbitone on acetylcholine (ACh) release from the rat frontal cortex using microdialysis. Ketamine 25, 50 and 100 mg kg-1 increased ACh release from the frontal cortex to 286%, 253% and 381% of basal release, respectively. In contrast, pentobarbitone 10, 20 and 40 mg kg-1 caused 73%, 78% and 96% inhibition of basal levels, respectively. The results suggest that ketamine and pentobarbitone have opposite effects on ACh release from the rat frontal cortex, as seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 7 publications
3
23
2
1
Order By: Relevance
“…Although cortical ACh decreases during administration of GABAergic anaesthetics, 16 33 34 the present findings show a significant increase in ACh concentrations during ketamine-induced unconsciousness. However, this increase was considerably lower than that reported by Kikuchi and colleagues 16 (∼105% in the present study vs ∼281% in the study by Kikuchi and colleagues). 16 We demonstrate that a dramatic increase (∼325%) in cortical ACh is associated with emergence and recovery, which could result from increased arousal because of decreased plasma ketamine concentrations.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Although cortical ACh decreases during administration of GABAergic anaesthetics, 16 33 34 the present findings show a significant increase in ACh concentrations during ketamine-induced unconsciousness. However, this increase was considerably lower than that reported by Kikuchi and colleagues 16 (∼105% in the present study vs ∼281% in the study by Kikuchi and colleagues). 16 We demonstrate that a dramatic increase (∼325%) in cortical ACh is associated with emergence and recovery, which could result from increased arousal because of decreased plasma ketamine concentrations.…”
Section: Discussioncontrasting
confidence: 90%
“…However, this increase was considerably lower than that reported by Kikuchi and colleagues 16 (∼105% in the present study vs ∼281% in the study by Kikuchi and colleagues). 16 We demonstrate that a dramatic increase (∼325%) in cortical ACh is associated with emergence and recovery, which could result from increased arousal because of decreased plasma ketamine concentrations. Higher ACh concentrations are typically correlated with an activated cortex, as in the waking state 35 or rapid eye movement sleep, 35 which is also characterized by decreased gamma coherence.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Jentsch et al (1998) reported that the acute administration of PCP in rats increases cortical acetylcholine (ACh) release measured by means of microdialysis. Similarly, Kikuchi et al (1997) reported substantial increases in frontal cortical ACh release following ketamine administration. These data, in concert with the finding that amphetamine also increases and, following repeated administration, sensitizes increases in cortical ACh release (Nelson et al 2000), suggest that increases in cortical cholinergic transmission may represent a common effect of psychotogenic treatments (see also Sarter et al 2001).…”
Section: Introductionmentioning
confidence: 88%
“…In addition, the central cholinergic system has been implicated in modulating the depressant action of pentobarbital. In vivo studies indicate that acute treatment with pentobarbital can inhibit Ach release and decrease muscarinic receptor binding in the frontal cortex, striatum and hippocampus of rats and mice (Inoue et al, 1992;Kikuchi et al, 1997;Sato et al, 1996). Intra-septal microinjection of arecoline is reported to significantly shorten the duration of pentobarbital-induced LORR (Zucker et al, 1987).…”
mentioning
confidence: 99%